Development and validation of an HPLC method to determine lasalocid in raw milk samples from dairy cows. - Jerez, Alejandro; Chihuailaf, Ricardo; Nella Gai, Maria; Noro, Mirela; Wittwer, Fernando (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The ionophore lasalocid has been approved for use as a ruminant feed additive in many countries. This paper describes a simple and rapid method for the determination of lasalocid in cow milk using high performance liquid chromatography with ultraviolet detection. The method is specific for the analysis of lasalocid in raw milk following a liquid-liquid extraction and was validated for the drug in bovine raw milk. The standard curve was linear from 0.5 to 3.0 Î¼g/mL Intra (7.2%) and inter (7.0%) day (d) precision and accuracy (84%) of the method were within the limits proposed by Food and Drug Administration in the Bioanalytical Method Validation Guidance. The stability of lasalocid was established during three freeze-thaw cycles and long-term stability at -30°C for 79 d. The sensitivity and simplicity of the method make it suitable for control of lasalocid residues in raw milk of dairy animals.